“Students’ perception about the use of clil methodology” - Casa Gualpa, Liliana Abigail (2023)
CLIL methodology is considered as an innovative method to teach the English language along with various subjects , the main objective was to describe the student’s perception about the use of CLIL (Content language and Integrate Learning) methodology in students of the third year of secondary education at Pujilí High school. The methodology used was quantitative, descriptive level, non-experimental. Data collection was done with a questionnaire adapted form (Syzdykbayeva, 2017), and validated by experts criteria. This study revealed that students' perceptions are based on the following aspects: motivation, content, and English language skills. These aspects showed that the students felt very satisfied learning English through the CLIL methodology. This allowed them to better develop their skills such as speaking, listening and their cultural knowledge. In addition to arousing the interest in learning the English language through different contents in which he was related to the Ecuadorian culture, thus creating motivation to learn culture and language at the same time. In conclusion, the CLIL methodology allowed students to develop language skills and cultural content, therefore, the researchers suggest including the methodology to provide a better learning experience for students.